2019
DOI: 10.1111/1365-2745.13287
|View full text |Cite
|
Sign up to set email alerts
|

The spatial complexity of seed movement: Animal‐generated seed dispersal patterns in fragmented landscapes revealed by animal movement models

Abstract: Large animals provide crucial seed dispersal services, yet face continued threats and are susceptible to changes in landscape composition and configuration. Thus, there is a growing imperative to improve understanding of animal‐generated seed dispersal using models that incorporate spatial complexity in a realistic, yet tractable, way. We developed a spatially explicit agent‐based seed dispersal model, with disperser movements informed by biotelemetry data, to evaluate how landscape composition and configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 85 publications
0
35
0
Order By: Relevance
“…Another potential area of application is in animal-mediated seed dispersal research, which has identified the need to integrate frugivory and disperser movement (Côrtes & Uriarte 2013). A recent study highlighted the implications of using generic phenomenological movement representations (e.g., correlated random-walk) on dispersal model outcomes, and suggested more processbased movement approaches (Nield et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential area of application is in animal-mediated seed dispersal research, which has identified the need to integrate frugivory and disperser movement (Côrtes & Uriarte 2013). A recent study highlighted the implications of using generic phenomenological movement representations (e.g., correlated random-walk) on dispersal model outcomes, and suggested more processbased movement approaches (Nield et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, differences in dispersal distance and disperser effectiveness between species have been studied among frugivorous bird and seed‐harvesting ant assemblages. Any further examination of mammal‐mediated fungal spore dispersal should consider the relatively large body of literature produced on seed dispersal (e.g., Cousens, Hill, French, & Bishop, 2010; Jones & Muller‐Landau, 2008; Lehouck et al., 2009; Levin et al., 2003; Levey et al., 2008; Muller‐Landau et al., 2008; Nield et al., 2020; Spiegel & Nathan, 2007; Will & Tackenberg, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although germination experiments would need the be conducted in order to confirm that the transported seeds are actually viable, we can expect that at least a portion of them will contribute to plant recruitment (Tella et al 2020). In a fragmented landscape like the wetlands, where ground connectivity between forest patches is restricted by flooded terrain, seed dispersal by terrestrial vertebrates is likely limited (Nield et al 2020). In this scenario, the presence of large bodied frugivorous birds such as the macaws can become vital to maintain gene flow between forest fragments, in particular of plant species with large seeds which cannot be transported by smaller birds (Baños-Villalba et al 2017).…”
Section: Final Remarksmentioning
confidence: 99%